Management of a case of acute bacterial cholangitis with septic shock in a surgical intensive care unit: A case report (Indian Journal of Case Reports, 2021)
Acute bacterial cholangitis is an emergency and needs prompt diagnosis and administration of appropriate therapy as soon as possible. The presentation of the condition may vary from case to case. As the mortality associated with this illness is huge, a thorough physical examination and high clinical suspicion may help in timely diagnosis and could be lifesaving. Our patient presented with sepsis and septic shock to the emergency department, on clinical examination, and point-of-care ultrasonography performed by a vigilant emergency team, and given high suspicion of cholangitis, the patient was redirected to surgical intensive care unit (SICU). In SICU, after initial resuscitation and stabilization, further diagnostic imaging studies were carried out and definitive interventional management was initiated by the multidisciplinary team of the hospital. The condition of the patient improved drastically on apt and targeted management. Hence, it is very important to rule out the possibility of acute cholangitis in patients presenting with septic shock with a suspected intra-abdominal source of infection. Acute bacterial cholangitis is a highly treatable condition with very encouraging outcomes on timely intervention and results in significantly reduced mortality, morbidity, length of hospital stay, and treatment cost of course.